HAMBATAN-HAMBATAN PENERAPAN ISAK 335 DALAM PENYUSUNAN LAPORAN KEUANGAN PADA MASJID AT-TAQWA BANJARMASIN - Mahyuni; Basyirah Ainun; Manik Mutiara Sadewa; Lusiana Handayani (P3M Politeknik Negeri Banjarmasin, 2025)
As a non-profit organization, mosques are expected to present financial statements in accordance with ISAK 35. However, the implementation of this standard at At-Taqwa Mosque Banjarmasin has not yet been optimal. This study aims to identify the problems encountered in the implementation of ISAK 35 in the preparation of mosque financial statements. This research employs a qualitative approach using interviews with mosque administrators and congregants. The findings reveal several obstacles, including the limited understanding of mosque administrators regarding financial transparency and accountability, insufficient knowledge of applicable accounting standards, and the absence of financial managers with an accounting background. In addition, the lack of demand from congregants for financial statements prepared in accordance with ISAK 35 contributes to the low motivation of mosque administrators to implement the standard.